25 Years of cooling research in office buildings: Review for the integration of cooling strategies into the building façade (1990–2014). (May 2017) - Prieto, Alejandro; Knaack, Ulrich; Klein, Tillmann; Auer, Thomas
Abstract: This paper seeks to present a panorama of cooling related research in office buildings, categorising reported research experiences from the past 25 years in order to identify knowledge gaps and define current paths and trends for further exploration. The general goal behind this research is to support the design of sustainable office buildings in warm climates through examination of past experiences, thus the paper focuses on strategies at building level and specially related with façade design. Peer reviewed journal articles were selected as the source for the study, given the reliability of the information published under peer-review processes. Several queries were carried out throughout three online journal article databases (Web of Science, SCOPUS and ScienceDirect), considering published papers from 1990 onwards. The resulting article database was then explored trough descriptive analysis and in-depth review of some articles to expand on specific topics in order to thoroughly visualise scientific interest and tendencies within the field of study for the last 25 years. As results of the review it is possible to state the high current relevance of cooling research, having experienced an increase of publications under different climate contexts and varied topics ranging from passive to solar cooling, which is seen as a research field on its own. Also, in terms of research methods, software simulations seem to be the primary tool for cooling research, which makes sense for performance driven developments. On the other hand, the main knowledge gaps identified are the need for specific research regarding possibilities for application and architectural integration of cooling systems; the lack of articles addressing some specific cooling strategies, such as the use of evaporative and ground cooling; and the need for more information about the operation of cooling systems, especially taking users' perception and their behaviour into account.